THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP OF SCHOOL ADMINISTRATORS AND ACADEMIC ADMINISTRATION UNDER THE OFFICE OF PHICHIT PRIMARY EDUCATIONAL SERVICE AREA 2 - Pradidwongwan, Thitima; Naebnean, Teerapod; Dee-Aim, Kraiwit (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
This research aimed to: 1) examine the level of transformational leadership among school administrators, 2) assess the level of academic administration, and 3) analyze the relationship between transformational leadership and academic administration. he sample consisted of 291 administrators and teachers selected using Krejcie and Morgan's table through stratified random sampling. The research instruments were questionnaires on transformational leadership and academic administration. The content validity (IOC) ranged from 0.67 to 1.00. The reliability of the transformational leadership questionnaire was 0.94, and for the academic administration questionnaire was 0.93. Data were analyzed using mean, standard deviation, and Pearson’s correlation.. The research findings revealed that: The level of transformational leadership of school administrators was at a high level overall. The highest mean was for intellectual stimulation ,followed by individualized consideration.The lowest-scoring dimension was inspirational motivation.2. The level of academic administration in schools was also at a high level. The highest mean was for learning process development , followed by educational media and technology . The lowest-scoring dimension was educational supervision .3. The relationship between transformational leadership and academic administration was positively high, with a Pearson correlation coefficient of 0.97. The highest correlation was found in curriculum development, while the lowest was in learning assessment and quality assurance system development, with statistical significance at the .01 level.